Legal Protection Against Status Determination of Suspects for Unpleasant Crimes After the Decision of the Constitutional Court Number 1/PUU-XI/2013 - Nugraha, Xavier; Setiawan, Peter Jeremiah; Serfiyani, Citi Rahmati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Article 335 paragraph (1) of the Criminal Code and Article 21 paragraph (4) of the Criminal Procedure Code are deemed to be contradicting Article 28D of the 1945 Constitution. Through the Decision of the Constitutional Court Number 1 / PUU-XI / 2013 excluding the phrase